Análise de Guias de Ondas Contendo Materiais Bi-isotrópicos pelo Método FDTD10.14209/jcis.2001.5 - Dimitri Sá de Alcantara, Licinius; Goncalves Farias, Rubem (Journal of Communication and Information Systems, 2015)
A numerical formulation based on the Finite-Difference Time-Domain (FDTD) method is fitted to simulate the electromagnetic waves propagation in waveguides containing bi-isotropic materials. This class of materials has been focusing the researchers interest along the last years due its special properties, especially regarding the chiral materials, which are characterized by generating an interdependence between propagation and polarization that brings a promising perspective concerning the spreading of new telecommunication devices.